Characteristics of Supply Relationships and related People Management Issues - Koulikoff-Souviron, Marie; Harrison, Alan (Cranfield University, 2003)
A large body of research exists on inter-organisational relationships and related concepts such as partnerships and strategic alliances. This is sometimes criticised for too much attention paid to the antecedents rather than to the management stage. Thus, Spekman et al. (1998) state: “It would appear that while academics purport to understand the concept of alliance formation, the practice of alliance management continues to pose a significant challenge” (p.7